1998
DOI: 10.1016/s0306-4522(97)00499-5
|View full text |Cite
|
Sign up to set email alerts
|

The pro-convulsant actions of corticotropin-releasing hormone in the hippocampus of infant rats

Abstract: Whole-cell patch-clamp and extracellular field recordings were obtained from 450-μm-thick brain slices of infant rats (10-13 days postnatal) to determine the actions of corticotropin-releasing hormone on glutamate-and GABA-mediated synaptic transmission in the hippocampus. Synthetic corticotropin-releasing hormone (0.15 μM) reversibly increased the excitability of hippocampal pyramidal cells, as determined by the increase in the amplitude of the CA1 population spikes evoked by stimulation of the Schaffer colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
116
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 24 publications
7
116
0
1
Order By: Relevance
“…32 More recently, in vitro studies have shown that CRH modulates glutamatergic mechanisms to increase excitatory neurotransmission in the hippocampal circuit. 6,25 Thus, under physiological circumstances, release of CRH may modulate hippocampal neurotransmission, augmenting glutamate-mediated alterations of hippocampal function. This may influence both normal hippocampal processes such as longterm potentiation and, when excessive, may promote abnormal excitation 1,6,25 and excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…32 More recently, in vitro studies have shown that CRH modulates glutamatergic mechanisms to increase excitatory neurotransmission in the hippocampal circuit. 6,25 Thus, under physiological circumstances, release of CRH may modulate hippocampal neurotransmission, augmenting glutamate-mediated alterations of hippocampal function. This may influence both normal hippocampal processes such as longterm potentiation and, when excessive, may promote abnormal excitation 1,6,25 and excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…6,25 Thus, under physiological circumstances, release of CRH may modulate hippocampal neurotransmission, augmenting glutamate-mediated alterations of hippocampal function. This may influence both normal hippocampal processes such as longterm potentiation and, when excessive, may promote abnormal excitation 1,6,25 and excitotoxicity. 9,36,37 The neuroanatomical basis for the influence of CRH on hippocampal neurotransmission has been explored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6A and B). When administered icv ('centrally'), CRH reaches the hippocampus [19] where it influences neurons directly [64,20]. Similar to the effects of early-life stress, these CRH-evoked deficits emerged later in adulthood, and were progressive.…”
mentioning
confidence: 99%